Narrow-band imaging in the prediction of surveillance intervals after polypectomy in community practice - Paggi, Silvia; Rondonotti, Emanuele; Amato, Arnaldo; Fuccio, Lorenzo; Andrealli, Alida; Spinzi, Giancarlo; Radaelli, Franco (Endoscopy, 2015)
Background and study aims: It has been proposed that the use of narrow-band imaging (NBI) for real-time histological assessment to determine postpolypectomy surveillance intervals is a cost-effective approach to the management of diminutive polyps. However, significant discrepancies in NBI performance have been observed among endoscopists; hence, professional societies recommend training, monitoring, and auditing. The aim of the present study was to evaluate the performance of real-time optical diagnosis for diminutive polyps after the inclusion of this approach in an internal quality assurance program, in order to assess its applicability in clinical practicePatients and methods: Four endoscopists attended periodic training sessions on NBI assessment of polyp histology before and during the study. Performance was audited and periodic feedback was provided. The accuracy of high-confidence NBI evaluation for polyps ≤ 5 mm in predicting surveillance intervals according to the European and US guidelines, and the negative predictive value (NPV) for adenoma in the rectosigmoid were calculated and compared with recommended thresholds (90 % agreement and 90 % NPV, respectively).Results: Overall, 284 outpatients (mean age 61.3 ± 18.2 years; 63 % males) were enrolled. A total of 656 polyps were detected, 465 of which (70.9 %) were diminutive (70.5 % adenomas). Sensitivity, specificity, positive and negative predictive values, and accuracy of high-confidence NBI predictions for adenoma in diminutive lesions were 95.3 %, 83.5 %, 93.5 %, 87.6 %, and 91.9 %, respectively. High-confidence characterization of diminutive polyps predicted the correct surveillance interval in 95.8 % and 93.3 % of cases according to European and American guidelines, respectively. NPV for adenoma in the rectosigmoid was 91.3 %Conclusions: For community settings in which endoscopists are adequately trained and performance is periodically audited, real-time optical diagnosis for diminutive polyps is sufficiently accurate to avoid postpolypectomy histological examination of resected lesions, or to leave rectosigmoid hyperplastic polyps in place.Trial registered at ClinicalTrials.gov (NCT02196402).